2003
DOI: 10.1002/cncr.11177
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a novel neoadjuvant and adjuvant hormone‐deprivation approach on quality of life, voiding function, and sexual function after prostate brachytherapy

Abstract: Two fully fluorinated polymers, poly(tetrafluoroethylene) (PTFE) membranes and poly(tetrafluoroethylene‐co‐hexafluoropropylene) (FEP) films, were modified by graft copolymerization with monoacryloxyethyl phosphate (MAEP) in an aqueous solution at ambient temperature using gamma irradiation. The modified membranes were characterized by XPS, FTIR, and phosphate analysis. A correlation between peak heights in the FTIR PAS spectra and the overall grafting yield was found. Neither the surface coverage (as obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Only Ng et al explored the functional consequences of RT therapy for PCa in PLWHA with the FACT-G survey and found patients to have a mean score of 80.1 with scores of 83, 80, and 74 for patients of subsets BT, BT+EBRT, and EBRT, respectively. This is comparable to the published rates between 66-85% from previous studies that utilized the same survey in PCa patients treated with BT, BT+EBRT, or EBRT alone (30,31,32). Furthermore, both Ng et al and these studies found that the overall quality of life was lower in patients treated with EBRT alone compared to treatment with BT alone.…”
Section: Discussionsupporting
confidence: 84%
“…Only Ng et al explored the functional consequences of RT therapy for PCa in PLWHA with the FACT-G survey and found patients to have a mean score of 80.1 with scores of 83, 80, and 74 for patients of subsets BT, BT+EBRT, and EBRT, respectively. This is comparable to the published rates between 66-85% from previous studies that utilized the same survey in PCa patients treated with BT, BT+EBRT, or EBRT alone (30,31,32). Furthermore, both Ng et al and these studies found that the overall quality of life was lower in patients treated with EBRT alone compared to treatment with BT alone.…”
Section: Discussionsupporting
confidence: 84%
“…It is well known that the FACT, the SF‐36 and the UCLA index are high‐quality questionnaires for evaluating the QOL of patients with urological cancer 5–9 . However, most published studies using the Japanese translation have concerned patients with early PC 7–9 .…”
Section: Discussionmentioning
confidence: 99%
“…Now, the Functional Assessment of Cancer Therapy (FACT), the Medical Outcomes Study short‐form 36‐item health survey (SF‐36), and the University of California Los Angeles (UCLA) index are available for high‐quality evaluation, 1–3 but there are few reports on the validation of the Japanese translations 4,5 . Most published studies concern patients with early PC 6–9 . However, there has been little attention paid to formal evaluation of QOL as a primary end‐point in stage D2 cases 10–13 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, decreased sexual function related to the temporary use of an LHRH agonist may be related to failure of the hypothalamicpituitary axis to recover [39,40] a year or more after stopping the drug, although there is controversy whether short duration (5-6 months) LHRH treatment has a significant effect on long-term potency [36]. Finally, newer approaches to androgen ablation using antiandrogens and finasteride have been reported which are not associated with any effect on short-or long-term HRQoL or sexual function [41], allowing the advantages of hormone manipulation in terms of tumour control without its disadvantage.…”
Section: Sexual Functionmentioning
confidence: 99%